2015
DOI: 10.1371/journal.pone.0136747
|View full text |Cite
|
Sign up to set email alerts
|

Routine Eye Screening by an Ophthalmologist Is Clinically Useful for HIV-1-Infected Patients with CD4 Count Less than 200 /μL

Abstract: ObjectiveTo investigate whether routine eye screening by an ophthalmologist in patients with HIV-1 infection is clinically useful.MethodsA single-center, retrospective study in Tokyo, Japan. HIV-1-infected patients aged over 17 years who visited our clinic for the first time between January 2004 and December 2013 and underwent full ophthalmologic examination were enrolled. At our clinic, ophthalmologic examination, including dilated retinal examination by indirect ophthalmoscopy was routinely conducted by opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
2
24
0
3
Order By: Relevance
“…When ruling out other ocular diseases was difficult, the response to syphilis treatment was also taken into account for the diagnosis of ocular syphilis. At our hospital, patients with HIV infection undergo routine ophthalmologic examination by an ophthalmologist that includes dilated retinal examination using indirect ophthalmoscopy, during the first visit to the clinic 10. If the diagnosis of ocular diseases cannot be confirmed, ophthalmological examination is repeated within 1–4 weeks 11.…”
Section: Methodsmentioning
confidence: 99%
“…When ruling out other ocular diseases was difficult, the response to syphilis treatment was also taken into account for the diagnosis of ocular syphilis. At our hospital, patients with HIV infection undergo routine ophthalmologic examination by an ophthalmologist that includes dilated retinal examination using indirect ophthalmoscopy, during the first visit to the clinic 10. If the diagnosis of ocular diseases cannot be confirmed, ophthalmological examination is repeated within 1–4 weeks 11.…”
Section: Methodsmentioning
confidence: 99%
“…As possible AE after 4 weeks following the last administration of Mog, two infectious complications were identified: CMV retinitis on day 42 in UPN‐01 and pneumocystis pneumonia on day 220 in UPN‐02. The reason for AE with Mog was that the absolute counts of CD4‐positive lymphocytes were 127/μL (UPN‐01) and 50/μL (UPN‐02) at the development of their infections, as previously reported …”
Section: Resultsmentioning
confidence: 54%
“…36 reported. 26,45,46 We then evaluated ≥grade 3 nonhematological toxicities after Mog or Len (Table 3). In nine patients who received Mog, one (11.1%, UPN-03) developed a skin rash on day 22 after Mog and required the systematic administration of steroids with symptomatic improvement.…”
Section: Infectious Complications and Nonhematological Toxicitymentioning
confidence: 99%
“…7 Many studies including Indian studies have concluded that heterosexual contact to be the most common mode of infection in HIV infection. [7][8][9][10] In present study half of the total patients had contacted HIV infection by heterosexual contact (51%). Remaining 49% had infection through other mode of infections.…”
Section: Discussionmentioning
confidence: 99%